Vanity fair: a novel without a hero - Thackeray, William Makepeace; Jerrold, Walter (J. M. Dent, 1901)
Scorned for her lack of money and breeding, Becky must use all her wit, charm and considerable sex appeal to escape her drab destiny as a governess. From London's ballrooms to the battlefields of Waterloo, the bewitching Becky works her wiles on a gallery of memorable characters, including her lecherous employer, Sir Pitt, his rich sister, Miss Crawley, and Pitt's dashing son, Rawdon, the first of Becky's misguided sexual entanglements.
Title within ornamental border.
Scorned for her lack of money and breeding, Becky must use all her wit, charm and considerable sex appeal to escape her drab destiny as a governess. From London's ballrooms to the battlefields of Waterloo, the bewitching Becky works her wiles on a gallery of memorable characters, including her lecherous employer, Sir Pitt, his rich sister, Miss Crawley, and Pitt's dashing son, Rawdon, the first of Becky's misguided sexual entanglements.
Keywords: Married women / Fiction.; Social classes / Fiction; Female friendship / Fiction.; British / Europe / Fiction; Waterloo, Battle of, Waterloo, Belgium, 1815 / Fiction; England / Fiction.; Fiction / fast / (OCoLC)fst01423787